The Federal Reserve as lender of last resort during the subprime crisis: Successful stabilisation without structural changes - Hansjörg Herr; Sina Rüdiger; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2016)
This paper studies the actions of the U.S. Federal Reserve Bank (FRB) during the financial crisis from 2007-2012 rating the performance of the Federal Reserve during the crisis. The chosen scoring model approach shows that the average performance of five specific measures taken by the FRB only ranks between fair and good. Comparing Stiglitz (2010) viewpoints with those of the FRB, this paper analyses several policies and events and argues that the resulting decisions were well intentioned but that the outcome was different from expectations because of missing regulations and restrictions. Furthermore, the structure of the FRB is examined and criticized.
Keywords: E42; E58; G18; E65; 330